Studi Keandalan Dan Evaluasi Sistem Kerja Rele Jaringan Transmisi 150 kV Koto Panjang - Pekanbaru - Ari Gustia Warman; Firdaus Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
In this case from topic Study of Reliability And Evaluation Work System Relay Protection of 150 kV Transmission Line Koto Panjang - Pekanbaru. In this study just concern about problem of GI Koto Panjang, GI and GI Bangkinang Garuda Sakti. Transmission has protecion used on the 150 kV such as Distance Rele and safety reserves of the OCR and GFR. This topic point to analyze used of Distance relays network of 150 kV, calculate the setting impedance relay distance and calculates the setting current and time on each other Bay transmision OCR and GFR in each - each other relay in each substation (Koto Panjang, Bangkinang, Garuda Sakti) reperesent well as the interruption of transmission in any history of interference. Observations and analysis in this study will be made in the form of reliability, the reliability of the system work in each transmission relay when an interruption occurs.Keywords: Relay Distance, OCR, GFR, Reliability, transmison of 150 kV.